2009
DOI: 10.1038/nchembio.208
|View full text |Cite
|
Sign up to set email alerts
|

Structure and allosteric effects of low-molecular-weight activators on the protein kinase PDK1

Abstract: Protein phosphorylation transduces a large set of intracellular signals. One mechanism by which phosphorylation mediates signal transduction is by prompting conformational changes in the target protein or interacting proteins. Previous work described an allosteric site mediating phosphorylation-dependent activation of AGC kinases. The AGC kinase PDK1 is activated by the docking of a phosphorylated motif from substrates. Here we present the crystallography of PDK1 bound to a rationally developed low-molecular-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
185
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(193 citation statements)
references
References 38 publications
8
185
0
Order By: Relevance
“…Importantly, our recent studies on PDK1 itself show that the ␣-C helix is extremely mobile in solution (39), incompatible with a stable ␣-helix observed in active crystal structures of protein kinases. In addition, deuterium exchange experiments in solution show that the binding of the C-terminal region of PRK2 (PIFtide) or small molecule compounds to the HM/PIFbinding pocket of PDK1 stabilizes the ␣-C helix, and prompts allosteric effects on the ATP binding site, thereby activating PDK1 (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, our recent studies on PDK1 itself show that the ␣-C helix is extremely mobile in solution (39), incompatible with a stable ␣-helix observed in active crystal structures of protein kinases. In addition, deuterium exchange experiments in solution show that the binding of the C-terminal region of PRK2 (PIFtide) or small molecule compounds to the HM/PIFbinding pocket of PDK1 stabilizes the ␣-C helix, and prompts allosteric effects on the ATP binding site, thereby activating PDK1 (39).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, deuterium exchange experiments in solution show that the binding of the C-terminal region of PRK2 (PIFtide) or small molecule compounds to the HM/PIFbinding pocket of PDK1 stabilizes the ␣-C helix, and prompts allosteric effects on the ATP binding site, thereby activating PDK1 (39). Thus, there is strong support for the mechanistic model by which the docking interaction of PRK2 to the HM/PIF-binding pocket on PDK1 would prompt an allosteric activation of PDK1 and in this manner support the phosphorylation of the activation loop of PRK2.…”
Section: Discussionmentioning
confidence: 99%
“…Although the most likely reason is the relatively low affinity of these unoptimized scaffolds, one cannot exclude the possibility that these chemotypes do not modulate the PDK1 functional activity despite their specific binding. At the present time, because of the low affinity of the allosteric ligands, both those discovered in this work and those described in the literature (15,16,37,38), any meaningful modulation studies in intact cells are deferred until more potent ligands are developed from these initial leads in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Several independent studies demonstrated that the PIF pocket is amenable to small molecule binding (15,16,37,38). Using a virtual screening approach of a ϳ60,000 compound chemical library, Engel et al (15) identified several compounds that increased the activity of ⌬PH-PDK1.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing precedent for development of allosteric kinase inhibitors, which have proven to be much more selective than classical ATP competitive inhibitors (21,(43)(44)(45)(46)(47)(48)(49). Allosteric modulation of kinases is particularly promising because many soluble kinases have inter-or intradomain associations that allosterically regulate kinase activity.…”
Section: Discussionmentioning
confidence: 99%